The Hanging Marriage Tradition in West Java from the Perspective of Law Number 16 of 2019 concerning Marriage - Rahmat Aripin; Aldo Aultar (Punggawa Law Review, 2026)
This study aims to analyze the tradition of hanging marriages, which is still practiced by some communities in West Java, from the perspective of Law Number 16 of 2019 concerning Marriage. Hanging marriages are marriage practices carried out through matchmaking and the binding of marital relations from childhood, while full household life is postponed until both partners are considered adults. This study uses a qualitative method with a library research approach. Data were obtained from various scientific literature, journals, books, laws and regulations, and previous research results, which were analyzed using a descriptive-analytical approach. The results show that the tradition of hanging marriages is maintained because it is considered able to maintain family honor, prevent promiscuity, adultery, and pregnancy outside of marriage. However, this practice also has various negative impacts, such as increased school dropout rates, the risk of poverty, divorce, domestic violence, and reproductive health problems due to early marriage. From the perspective of Law Number 16 of 2019, the minimum age of marriage for men and women is 19 years to ensure the physical, mental, and social maturity of the prospective bride and groom. Therefore, the practice of hanging marriages involving minors is inconsistent with child protection goals and the principles of national marriage law. Customary traditions can be maintained as long as they do not conflict with laws and children's rights